2004
DOI: 10.1023/b:boun.0000020160.28184.a0
|View full text |Cite
|
Sign up to set email alerts
|

Organised Motion and Radiative Perturbations in the Nocturnal Canopy Sublayer above an Even-Aged Pine Forest

Abstract: Using time series measurements of velocity, carbon dioxide and water vapour concentration, and temperature collected just above a 15 m tall even-aged pine forest, we quantify the role of organized motion on scalar and momentum transport within the nocturnal canopy sublayer (CSL). We propose a framework in which the nocturnal CSL has two end-members, both dominated by organised motion. These end-members represent fully developed turbulent flows at near-neutral or slightly stable stratification and no turbulence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(96 citation statements)
references
References 41 publications
4
89
0
3
Order By: Relevance
“…Using the canopy height h c instead of the measurement height z, the normalized frequency values at which the cospectra peak, occur at 0.6 for both sites, which indicates that the most energetic eddies scale with h c and that for the selected cases the ratios U hc /U are invariant between the two sites. While such a simple cospectral model described very well the sensible heat cospectra measured during daytime, it was found unsuitable for fitting the night-time measured cospectra, which were often characterized by larger uncertainty as a result of multi-scale non-stationary processes usually affecting the night-time scalar transport in the sub-canopy layer (Cava et al, 2004).…”
Section: Cospectramentioning
confidence: 99%
“…Using the canopy height h c instead of the measurement height z, the normalized frequency values at which the cospectra peak, occur at 0.6 for both sites, which indicates that the most energetic eddies scale with h c and that for the selected cases the ratios U hc /U are invariant between the two sites. While such a simple cospectral model described very well the sensible heat cospectra measured during daytime, it was found unsuitable for fitting the night-time measured cospectra, which were often characterized by larger uncertainty as a result of multi-scale non-stationary processes usually affecting the night-time scalar transport in the sub-canopy layer (Cava et al, 2004).…”
Section: Cospectramentioning
confidence: 99%
“…The first reason is to eliminate nonturbulent conditions. For example, Cava et al [2004] showed how canopy waves are generated and how they can transport significant CO 2 inside to outside and outside to inside the canopy and over periods that if not properly captured by the averaging interval can lead to negative CO 2 fluxes (i.e., photosynthesis like) at night. Employing a u* threshold is primarily to ensure that runs collected under such nonturbulent conditions are removed.…”
Section: A2 Determination Of Closure Constants and The Stability Depmentioning
confidence: 99%
“…Often, nocturnal conditions are dominated by vertical subsidence, lack of steadiness in mean atmospheric conditions, and intermittent turbulent transport often initiated by transients such as passage of clouds [Cava et al, 2004]. When viewed from the onedimensional vertically integrated scalar continuity equation, these factors contribute to increased ''decoupling'' between the desired R E quantity and the CO 2 flux above the canopy, the latter being the observed quantity by EC methods.…”
Section: Introductionmentioning
confidence: 99%
“…Os valores médios de ECT, por escala, na estação úmida, durante a tarde, são maiores que os observados no período da manhã. Em todos os gráficos da Figura 2, entre as escalas 5 (~26,8 min) e 10 (~8,56 min), se observam mínimos relativos associados à existência da falha espectral indicando possível ocorrência de ondas de gravidade acima da copa florestal (Cava et al, 2004). Na estação seca os valores médios das ECTs, por escala temporal, durante a noite, são maiores que aqueles da madrugada.…”
Section: Resultsunclassified